Sean's Self Confidence And Spirit In Finding His Grandfather In Journey2: The Mysterious Island Movie (2012) Directed By Brad Peyton: An Individual Psychological Approach - Susanti, Yesi; , Drs. Abdillah Nugroho, M. Hum; , Dr. Phil. Dewi Candraningrum, S.Pd., M.Ed (2013)
The study is to reveal how is the major character‟s self confidence and spirit is reflected in Journey to the Mysterious Island directed by Brad Peyton published in 2012. The objective of the study is to analyze the structural elements in the movie and to analizeself confidence and spirit of the movie based on individual psychological approach. The researcher employs the descriptive qualitative research as a type of the research. The data sources divided into two, namely primary data source and secondary data source. The primary data source is the events of the movie and script of Journey to the Mysterious Island and the secondary data source is biography of character. The method of collecting data is documentation. The technique of analyzing data is descriptive. The result of the study is as follows. First, based on the structural analysis, Sean Anderson delivers a moral message that everybody should has self confidence and spirit to achieve the goal of life and the structural elements are related to each other and form a unity. Second, based on the individual psychological analysis, the writer concludes that to achieve the goal of life everybody needs desire, self confidence, spirit, and effort. They are the main key to achieve the goal of life and to get the good result.